Angelomorphic christology : antecedents and early evidence - Gieschen, Charles A. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1998)
This study demonstrates that angel and angel-related traditions, especially those growing from the so-called "Angel of the Lord" in the Hebrew Bible, had a significant impact on the origins and early development of Christology to the point that an Angelomorphic Christology is discernable in several first century texts. Significant effort is given to tracing the antecedents of this Christology in the angels and divine hypostases of the Hebrew Bible and Second Temple Jewish literature. The primary content of this volume is the presentation of pre-150 CE textual evidence of Angelomorphic Christology. This religio-historical study does not spawn a new Christology among the many scholarly "Christologies" already extant. Instead, it shows the interrelationship of various Christological trajectories and their adaptation from Jewish angelomorphic traditions.